2001
DOI: 10.1007/s002640000209
|View full text |Cite
|
Sign up to set email alerts
|

Femoral head fractures

Abstract: This report includes six patients with femoral head fractures. Five were associated with posterior hip dislocation, of which one also had an ipsilateral trochanteric fracture. All were young adults who had been injured in automobile accidents. The protocol for management, indications for surgery and guidelines for evaluation of results are described.Résumé Présentation de 6 cas de fracture de la tête fé-morale. Cinq associaient à la fracture une luxation posté-rieure de la hanche et l'un d'eux associait aussi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Preservation of oxygenation with the trochanteric flip was similar to that observed with the anterolateral approach, but with less variation during the procedure. Both of these approaches were superior in terms of oxygenation preservation to the posterior approach [8] 1996 Case series / IV 33 OP + NOP Anterior (10) 7 (70%) 1 (10%) Posterior (21) 13 (62%) 2 (11%) Stannard et al [12] 2000 Case series / IV 22 OP S-P (9) 0 1 (11.1%) K-L (12) 0 4 (33.3%) A + P (1) 0 0 Mostafa [9] 2001 Case series / IV 6 OP + NOP Lateral (4) 0 0 Posterior (1) 0 1 Kloen et al [7] 2002 Case series / IV 33 OP + NOP A-L (5) 3 (60%) 0 K-L (9) 4 (44.4%) 1 (11.1%) S-P (7) 2 (28.6%) 0 [TOF 5]* [4 (80%)]* 0 NOP (7) 0 1 (14.3%) Prokop et al [11] 2005 Case series / IV 9 OP K-L (9) 3 (33.3%) 1 (11.1%) Henle et al [6] 2007 Case series / IV 12 OP TOF (12) 4 (33.3%) 2 (16.7%) Solberg et al [15] 2009 Case series / IV 12 OP TOF (12) 4 (33.3%) 1 (8.3%)…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of oxygenation with the trochanteric flip was similar to that observed with the anterolateral approach, but with less variation during the procedure. Both of these approaches were superior in terms of oxygenation preservation to the posterior approach [8] 1996 Case series / IV 33 OP + NOP Anterior (10) 7 (70%) 1 (10%) Posterior (21) 13 (62%) 2 (11%) Stannard et al [12] 2000 Case series / IV 22 OP S-P (9) 0 1 (11.1%) K-L (12) 0 4 (33.3%) A + P (1) 0 0 Mostafa [9] 2001 Case series / IV 6 OP + NOP Lateral (4) 0 0 Posterior (1) 0 1 Kloen et al [7] 2002 Case series / IV 33 OP + NOP A-L (5) 3 (60%) 0 K-L (9) 4 (44.4%) 1 (11.1%) S-P (7) 2 (28.6%) 0 [TOF 5]* [4 (80%)]* 0 NOP (7) 0 1 (14.3%) Prokop et al [11] 2005 Case series / IV 9 OP K-L (9) 3 (33.3%) 1 (11.1%) Henle et al [6] 2007 Case series / IV 12 OP TOF (12) 4 (33.3%) 2 (16.7%) Solberg et al [15] 2009 Case series / IV 12 OP TOF (12) 4 (33.3%) 1 (8.3%)…”
Section: Discussionmentioning
confidence: 99%
“…Mostafa [3] and Vielpeau et al [6], respectively, reported 1 of 6 cases and 1 of 32 cases of such fractures occurring in the absence of hip dislocation; there was no further description of the lesions. Fabre et al [7] and Kim et al [8] reported two cases of simultaneous femoral head and neck fractures without associated dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…They occur more often in the context of a posterior hip dislocation [1][2][3][4][5][6], although there have been reports of rare cases following anterior dislocation [1,6], and exceptional cases without any dislocation [3,[6][7][8][9]. We report a Pipkin type II femoral head fracture that occurred in the context of a posterior hip subluxation.…”
Section: Introductionmentioning
confidence: 99%
“…Definitive fixation is subsequently performed with interfragmentary lag screws. In addition to burying pins or screws, some fractures are amenable to lag fixation from a non-articular entry point [35]. Multiple implant options have been described and include countersunk interfragmentary lag screws, selfcompression headless screws [36,37], or bio-absorbable pins or screws [38].…”
Section: Fragment Excision Versus Internal Fixationmentioning
confidence: 99%